HUBUNGAN "EVA" (ECONOMIC VALUE ADDED) DENGAN NILAI PERUSAHAAN DAN KEMAKMURAN PEMEGANG SAHAM PADA PERUSAHAAN MANUFAKTUR DAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK JAKARTA - Dewi, Sandra (jurnal ekonomi, 2007)
One of the measurement form on the basis of this value is Economic Value Added (EVA). EVA is selisis between capital rate of return with capital expense, and multiplied with economic book value of capital. In this research of company value and prosperity of the stockholder represented by market value added (MVA), Abnormal Return (A) and Proportion total liabilities to capital (D/V). Is therafore required by calculation of wich can measure company's finance performance precisely paid attention fully creditor expectation adn decision and stockholder.